Abnormal Graphitization Behavior in Near‐Surface/Interface Region of Polymer‐Derived Ceramics. Issue 5 (29th November 2022) - Wu, Chao; Lin, Fan; Pan, Xiaochuan; Chen, Guochun; Zeng, Yingjun; Xu, Lida; He, Yingping; Chen, Qinnan; Sun, Daoheng; Hai, Zhenyin
Abstract: The in situ free carbon generated in polymer‐derived ceramics (PDCs) plays a crucial role in their unique microstructure and resultant properties. This study advances a new phenomenon of graphitization of PDCs. Specifically, whether in micro‐/nanoscale films or millimeter‐scale bulks, the surface/interface radically changes the fate of carbon and the evolution of PDC nanodomains, promotes the graphitization of carbon, and evolves a free carbon enriched layer in the near‐surface/interface region. Affected by the enrichment behavior of free carbon in the near‐surface/interface region, PDCs exhibit highly abnormal properties such as the skin behavior and edge effect of the current. The current intensity in the near‐surface/interface region of PDCs is orders of magnitude higher than that in its interior. Ultrahigh conductivity of up to 14.47 S cm −1 is obtained under the action of the interface and surface, which is 5–8 orders of magnitude higher than that of the bulk prepared under the same conditions. Such surface/interface interactions are of interest for the regulation of free carbon and its resultant properties, which are the core of PDC applications. Finally, the first PDC thin‐film strain gauge that can survive a butane flame with a high temperature of up to ≈1300 °C is fabricated. Abstract : This study discovers a new phenomenon of graphitization of polymer‐derived ceramic (PDC). No matter in micro‐/nanoscale films or millimeter‐scale bulks, the surface/interface dramatically changes the evolution of carbon form in PDC, resulting in a free carbon enriched layer in the near‐surface/interface region. This reverses the understanding of the nanodomain structure and resultant properties of PDC.